2017
DOI: 10.1021/acs.orglett.7b02177
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis and N-Methyl-d-aspartate (NMDA) Receptor Activity of Ketamine Metabolites

Abstract: Ketamine is rapidly metabolized in the human body to a variety of metabolites, including the hydroxynorketamines. At least two hydroxynorketamines have significant antidepressant action in rodent models, with limited action against the N-methyl-D-aspartate (NMDA) receptor. The synthesis of 12 hydroxynorketamines and their binding affinity to the NMDA receptor is presented here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 23 publications
3
64
0
1
Order By: Relevance
“…Although NMDAR inhibition was long assumed to underlie ketamine’s antidepressant actions, recent evidence indicates that additional downstream mechanisms are likely to be involved. Indeed, it was recently shown that the ( 2S,6S;2R,6R )-HNK metabolite of ketamine is essential for its antidepressant actions and that ( 2R,6R )-HNK possesses robust antidepressant efficacy with low potency at the NMDAR [45, 107, 108, 353, 354]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although NMDAR inhibition was long assumed to underlie ketamine’s antidepressant actions, recent evidence indicates that additional downstream mechanisms are likely to be involved. Indeed, it was recently shown that the ( 2S,6S;2R,6R )-HNK metabolite of ketamine is essential for its antidepressant actions and that ( 2R,6R )-HNK possesses robust antidepressant efficacy with low potency at the NMDAR [45, 107, 108, 353, 354]. …”
Section: Discussionmentioning
confidence: 99%
“…(2017) [105] did not observe significant antidepressant behavioral actions using a single dose of ( 2R,6R )-HNK (i.e., 10 mg/kg) following chronic social defeat stress in mice and the same group reported no effects of ( 2R,6R )-HNK in the learned helplessness paradigm in rats [106], highlighting that further studies are required to establish the effective doses of this metabolite in different animal tests predictive of antidepressant efficacy. Importantly, ( 2R,6R )-HNK does not inhibit the NMDAR at antidepressant-relevant concentrations, as was demonstrated by a lack of MK-801 displacement binding studies (Inhibitory constant: Ki > 100 μM; half maximal inhibitory concentration: IC 50 > 100 μM), lack of functional activity on NMDARs localized in stratum radiatum interneurons in rat hippocampal slices or dissociated primary cell culture [45, 107109]. However, it does result in modest inhibition of mEPSC-NMDAR responses in mouse hippocampal cell cultures at higher concentrations [i.e., 50 μM; 108].…”
Section: Mechanisms Underlying Fast/rapid Onset Antidepressants Acmentioning
confidence: 99%
“…( S )-ketamine has ~4-fold greater affinity/potency at inhibiting the NMDAR compared to its ( R )-ketamine enantiomer 13, 111115 . Hashimoto and colleagues were the first to report superior and longer-lasting antidepressant actions of ( R )-ketamine compared with ( S )-ketamine in rodent models 116118 .…”
Section: Nmdar Inhibition-independent Mechanismsmentioning
confidence: 99%
“…[ 3 H]-MK-801 binding displacement studies showed that the affinity of ( 2R,6R )-HNK to displace MK-801 from the NMDAR is >100 μM, and that of ( 2S,6S )-HNK is 7–20 μM 111, 112 . In addition, at 10 μM concentration, ( 2R,6R )-HNK does not functionally inhibit the NMDARs localized at stratum radiatum interneurons in hippocampal slices, compared to ~50% inhibition by ketamine at this concentration 13 .…”
Section: Nmdar Inhibition-independent Mechanismsmentioning
confidence: 99%
“…They have also been used as deuterated drugs for the optimization of metabolic and safety profiles of ketamine, leveraging the kinetic isotope effect of deuterium. Despite the existence of a number of cold synthetic approaches to ketamine and norketamine, [8][9][10][11][12][13][14][15][16] there appear to be no examples in the literature of radiolabeling at any metabolically stable positions, namely, the cyclohexyl or phenyl positions. 6,7 Ketamine itself undergoes N-demethylation in vivo as part of its biotransformation, making carbon-14 labeling at the N-methyl position unsuitable for longer duration studies.…”
Section: Introductionmentioning
confidence: 99%